Filipino to English transfer errors in writing among college students: Implications for the senior high school English curriculum - Tanpoco, Manuel R. (Animo Repository, 2019)
Language transfer is an invasive term that has led to varied interpretations and research practices of it. This paper attempted to find out interlanguage transfer errors evident in the written outputs of CEU's three bigger schools/colleges and their implications to the new educational program of the Philippines, The Senior High School of the K to 12. Oral communication makes sense in a dialogue; it is a back and forth negotiation of meanings between the communicators. On the other hand, written communication is read; therefore misinterpretations of the meanings of the message being transferred are unavoidable and sometimes worsened (Penman, 1998). This paved a way for the researcher to explore lapses in students' written discourse, particularly, those which are transferred from L1 to L2. This study determined the types and extent of transfer errors in the written compositions of the student-respondents through Error Analysis (EA) and was found out to have been contaminated with errors in grammar, lexical choice, semantics and mechanics. Grammatical errors were found to be most prevalent especially in verb, pronoun and preposition usage; the other types of transfer errors such as lexical, semantics, and mechanics do not show much problem; students enrolled in different programs showed varying language needs as revealed by the type and extent of occurrence of transfer errors in their written compositions. Through the findings and conclusions drawn from this study, the researcher recommends that curriculum planners of the K to 12 program consider the implications yielded by the result of analysis of this study in their preparation/ revision of the basic education curriculum for the Senior High School. Furthermore, the researcher encourages the basic education teachers and college instructors of English to intensify the teaching of grammar, reading comprehension to reconcile meanings and enrich vocabulary loading, and improve spelling to avoid recurring transfer errors among their students' written outputs. © 2019 Asian E F L Journal Press. All rights reserved.